Genetic Diversity and Selection of Plasmodium vivax Apical Membrane Antigen-1 in China–Myanmar Border of Yunnan Province, China, 2009–2016 - Cui, Yan-Bing; Shen, Hai-Mo; Chen, Shen-Bo; Kassegne, Kokouvi; Shi, Tian-Qi; Xu, Bin; Chen, Jun-Hu; Wu, Jia-Hong; Wang, Yue (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium vivax apical membrane antigen-1 (PvAMA-1) is an important vaccine candidate for vivax malaria. However, antigenic variation within PvAMA-1 is a major obstacle to the design of a global protective malaria vaccine. In this study, we analyzed the genetic polymorphism and selection of the PvAMA-1 gene from 152 P. vivax isolates from imported cases to China, collected in the China–Myanmar border (CMB) area in Yunnan Province (YP) during 2009–2011 (n = 71) and 2014–2016 (n = 81), in comparison with PvAMA-1 gene information from Myanmar (n = 73), collected from public data. The overall nucleotide diversity of the PvAMA-1 gene from the 152 YP isolates was 0.007 with 76 haplotypes identified (Hd = 0.958). Results from the population structure suggested three groups among the YP and Myanmar isolates with optimized clusters value of K = 7. In addition, YP (2014–2016) isolates generally lacked some K components that were commonly found in YP (2009–2011) and Myanmar. Meanwhile, PvAMA-1 domain I is found to be the dominant target of positive diversifying selection and most mutation loci were found in this domain. The mutation frequencies of D107N/A, R112K/T, K120R, E145A, E277K, and R438H in PvAMA-1 were more than 70% in the YP isolates. In conclusion, high genetic diversity and positive selection were found in the PvAMA-1 gene from YP isolates, which are significant findings for the design and development of PvAMA-1-based malaria vaccine.